APLIKASI PANDUAN UNTUK MENGENAL TANAMAN OBAT BERBENTUK RIMPANG BERBASIS IMAGE PROCESSING MENGGUNAKAN METODE VGG16 - Aldi Budi Rianta; Dwi Intan Af'idah; Ardi Susanto (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Biodiversity in Indonesia, especially in medicinal plants with rhizome forms, is the focus of this research. With diverse geographical conditions, Indonesia possesses a wealth of traditional medicinal plant species. Previous studies have indicated limitations in manual plant identification, prompting the need for technology to support plant recognition. This research develops a guide application based on image processing using the VGG16 method to identify medicinal plants with rhizome forms. The methodology involves dataset collection, image preprocessing, VGG16 implementation, model evaluation using a confusion matrix, and application development. Black box testing of the application demonstrates success in plant identification, interface responsiveness, and data security. Results of image analysis and application development show optimal performance. Thus, this application can be considered successful in supporting the recognition of medicinal plants with rhizome forms.